Man as open essence. an approach to Xavier Zubiri’s theory of the person - Pérez Téllez, Javier Eduardo (2021)
This article aims to provide the reader with an approach to a bounded aspect of the thought of the Spanish philosopher Xavier Zubiri (1898-1983). Particularly, it seeks to explore Zubiri’s philosophical anthropology by means of the analysis of his concept of personal reality. Given that, for this author, ontology and philosophical anthropology are interrelated terms, the text offers a brief review of Zubiri’s conception of reality, and how it makes itself present to human beings understood as animal of realities. By means of the recognition of reality as existent by itself, it ispossible to gain access to the modus existendi of the human person and to its main characters: open essence and ‘suidad’.